2014
DOI: 10.1080/02705060.2014.893544
|View full text |Cite
|
Sign up to set email alerts
|

Effects of landscape factors and hydroperiod on aquatic macroinvertebrates with different dispersal strategies in southern Brazil ponds

Abstract: Ponds represent discrete sites surrounded by a terrestrial landscape that is inhospitable for aquatic macroinvertebrates. Such ecosystems are appropriate for testing the influence of area, isolation, and correlated variables such as habitat diversity and hydroperiod, on aquatic macroinvertebrate communities. We tested three hypotheses in natural and non-impacted ponds located in a matrix of coastal dunes without human interference in southern Brazil: (1) area, habitat diversity, and hydroperiod increase the to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…For instance, two of the generalist species recorded in this study, Leptodactylus latinasus and L. mystacinus , are abundant in rice cultivation fields in the Pampa biome and may benefit from habitat modifications in Pampa wetlands (Machado & Maltchik, 2010). Biotic homogenization of ponds is an important issue in the SBG, as about 90% of wetlands in southern Brazil are already fragmented (Maltchik, 2003; Maltchik, Costa, Becker, & Oliveira, 2003) and threatened by agricultural expansion (e.g., soy and rice), urban development, pollution, and invasion of pines (Grasel, Mormul, Bozelli, Thomaz, & Jarenkow, 2018; Machado, Drummond, & Paglia, 2008; Maltchik et al, 1996; Moraes, Stenert, Rolon, & Maltchik, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, two of the generalist species recorded in this study, Leptodactylus latinasus and L. mystacinus , are abundant in rice cultivation fields in the Pampa biome and may benefit from habitat modifications in Pampa wetlands (Machado & Maltchik, 2010). Biotic homogenization of ponds is an important issue in the SBG, as about 90% of wetlands in southern Brazil are already fragmented (Maltchik, 2003; Maltchik, Costa, Becker, & Oliveira, 2003) and threatened by agricultural expansion (e.g., soy and rice), urban development, pollution, and invasion of pines (Grasel, Mormul, Bozelli, Thomaz, & Jarenkow, 2018; Machado, Drummond, & Paglia, 2008; Maltchik et al, 1996; Moraes, Stenert, Rolon, & Maltchik, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Differences in numerical resolution may constitute an especially important issue for the study of community structure in freshwater wetlands because the invertebrate communities are usually numerically dominated by a few taxa such as chironomids, oligochaetes and microcrustaceans (e.g. Kratzer and Batzer, 2007 ; Moraes et al, 2014 ), which are the same taxa that are rarely classified with a fine taxonomic resolution.…”
Section: Introductionmentioning
confidence: 99%
“…The influence of hydroperiod on macroinvertebrate communities in non-permanently ponded wetlands is evident not only in prairiepothole wetlands of the NPPR, but globally. For example, research in southern Brazil concluded that hydroperiod affected macroinvertebrate richness, abundance and composition (Moraes, Stenert, Rolon, & Maltchik, 2014). Similarly, hydroperiod has been deemed an important structuring component of macroinvertebrates in Mediterranean climates in both Australia (Sim et al, 2013) and Spain (Boix, Sala, Quintana, & Moreno-Amich, 2004).…”
mentioning
confidence: 99%